2022
DOI: 10.3389/fvets.2022.963205
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal infrared thermography images in the hypothermic ruminant model: Anatomical-morphological-physiological aspects and mechanisms for thermoregulation

Abstract: Hypothermia is one factor associated with mortality in newborn ruminants due to the drastic temperature change upon exposure to the extrauterine environment in the first hours after birth. Ruminants are precocial whose mechanisms for generating heat or preventing heat loss involve genetic characteristics, the degree of neurodevelopment at birth and environmental aspects. These elements combine to form a more efficient mechanism than those found in altricial species. Although the degree of neurodevelopment is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 111 publications
2
28
0
Order By: Relevance
“…Moreover, calf–dam interaction can also compensate for hypothermia and prevent its physiologic consequences [ 67 ]. These results confirm that maternal care is a crucial factor affecting the survival of the offspring [ 21 , 131 ].…”
Section: Factors That Contribute To the Survival Of The Offspringsupporting
confidence: 73%
See 1 more Smart Citation
“…Moreover, calf–dam interaction can also compensate for hypothermia and prevent its physiologic consequences [ 67 ]. These results confirm that maternal care is a crucial factor affecting the survival of the offspring [ 21 , 131 ].…”
Section: Factors That Contribute To the Survival Of The Offspringsupporting
confidence: 73%
“…The ability to stand up for colostrum consumption participates in the thermoregulation of buffaloes [ 125 , 131 , 132 , 133 ]. Colostrum intake is a crucial element for the survival of newborn ruminants and largely depends on adequate imprinting mechanisms immediately after calving [ 26 ].…”
Section: Factors That Contribute To the Survival Of The Offspringmentioning
confidence: 99%
“…It has been suggested that hypothermia occurs immediately after birth as a protective mechanism to prevent hypoxic damage in the neonate and reduce the metabolic rate to improve the survival of the newborn in the first hours [ 19 , 20 , 21 ]. Another important risk factor for neonatal mortality in diverse species, such as humans, pigs, and cattle, is low birth weight [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from facial regions indicates that they can be used as thermal windows to determine physiological parameters such as body temperature and respiratory rate, which can help verify individuals’ health status [ 67 , 68 , 69 ]. One example is the case of water buffaloes, a species for which the thoracic window has been proposed to evaluate thermal comfort [ 70 , 71 ]. Body windows, like the thoracic region, have been mainly used to identify and follow up on inflammatory processes and infectious diseases, where IRT can assist by monitoring lesions and achieving timely diagnoses of hyperemia and hypothermia disorders [ 70 , 71 ].…”
Section: Body Windowsmentioning
confidence: 99%
“…One example is the case of water buffaloes, a species for which the thoracic window has been proposed to evaluate thermal comfort [ 70 , 71 ]. Body windows, like the thoracic region, have been mainly used to identify and follow up on inflammatory processes and infectious diseases, where IRT can assist by monitoring lesions and achieving timely diagnoses of hyperemia and hypothermia disorders [ 70 , 71 ].…”
Section: Body Windowsmentioning
confidence: 99%